Chad - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Chad’s risks of external and overall debt distress are high but have nonetheless declined in the past year. All but one external debt sustainability indicators are below their respective thresholds from 2019 onwards. The debt-to-revenue ratio moderately breaches its threshold under the baseline scenario. Overall, total public debt vulnerabilities are elevated although the present value (PV) of the public debt-to-GDP ratio remains on a downward trajectory. The debt sustainability analysis is based on projected continued fiscal prudence and an increase in non-oil revenues. Following the restructuring in 2018, the new Glencore debt contract has helped contain the impact of low oil prices on debt sustainability, as it allows for lower debt service when oil prices are lower.